Relações entre as teorias e as práticas curriculares na educação superior: um estudo no curso de graduação em administração da UFES - Pugliesi, Priscila Santos (2016)
The teaching-learning processes, in higher education, seek to unite the expertise and skills to the development of professional activities demanded by society and the formation of citizens who are able to respond to the concerns of the community in which they live. So, if on the one hand society requires increasingly skilled professionals and updated, educational institutions must be prepared to train these professionals. It is in this scenario that this research seeks to clarify the following problem: how the disciplines of administration of the Ufes converge theory and practice in the teaching-learning process? Thus, defined as general objective to understand the process of formation of grad skills at night of Administration course Ufes. By a result were established some specific objectives, which are: to analyse the adherence of the Resolution nº 4, of 13 July 2005, the Board of higher education of the National Council of education, investigate the perceptions of graduates relative to the content of the disciplines studied and their contributions to the development of skills and compare the possible competences developed in the framework of the course with the required by the labour market in the perception of the alumnus. The study was limited to night Administration course, which is still forming its first classes in order to meet as they are integrated with theory and practice in the classroom, in a manner that meets the aspirations of the student, while the public network user, to whom the University provides its services. The approach used in this study is quantitative and qualitative in nature. The types of research, in relation to the procedures that were used in this work are: case study through the analysis of the PPC and curricular matrix; descriptive research, by means of the questionnaire; explanatory research, through documents and the laws, and the essay, through the survey of material produced by other authors. The curriculum matrix analysis revealed that no jurisdiction has been worked satisfactorily during the course. The statistical analysis revealed that some competencies were worked in addition to the requirement of the labour market, to the detriment of others.